2022
DOI: 10.1039/d2ra06010h
|View full text |Cite
|
Sign up to set email alerts
|

UV-curable self-matting waterborne polyurethane acrylate coatingviaself-wrinkled surface during curing in open-air

Abstract: UV-curable self-matting coatings with self-wrinkled surface during UV-curing in open-air based on the balance between polymerization and oxygen inhibition rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 57 publications
2
4
0
Order By: Relevance
“…The 172 nm UV penetration is not strong enough to penetrate the wet film completely, only a gradient curing film is generated on the surface, as shown in Figure 3(Aa,Ab). As the curing process progresses, pressure stress builds up inside the system due to the varying degrees of curing According to previous research, we also found that the gloss value of films at 85 • geometry increased with increasing PI concentration, which was related to the morphology of surface wrinkles of the film [15]. The mechanism of preparing the self-matting coating using dual-UV curing technology is illustrated in Figure 3A.…”
Section: Gloss and Micromorphologysupporting
confidence: 62%
See 4 more Smart Citations
“…The 172 nm UV penetration is not strong enough to penetrate the wet film completely, only a gradient curing film is generated on the surface, as shown in Figure 3(Aa,Ab). As the curing process progresses, pressure stress builds up inside the system due to the varying degrees of curing According to previous research, we also found that the gloss value of films at 85 • geometry increased with increasing PI concentration, which was related to the morphology of surface wrinkles of the film [15]. The mechanism of preparing the self-matting coating using dual-UV curing technology is illustrated in Figure 3A.…”
Section: Gloss and Micromorphologysupporting
confidence: 62%
“…Thus, these results could offer valuable insights into the practical applications of wood coatings. According to previous research, we also found that the gloss value of films at 85° geometry increased with increasing PI concentration, which was related to the morphology of surface wrinkles of the film [15]. The mechanism of preparing the self-matting coating using dual-UV curing technology is illustrated in Figure 3A.…”
Section: Gloss and Micromorphologysupporting
confidence: 60%
See 3 more Smart Citations